2008
DOI: 10.1111/j.1748-5967.2008.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of Hymenoptera and Diptera pollinators in onion (Allium cepa L.) pollination

Abstract: Onion (Allium cepa L.) is protandrous in nature and requires cross‐pollination to avoid inbreeding. The pollination potential of native bees (Hymenoptera) and true flies (Diptera) was assessed in the perspective of finding the best pollinators for onion cross‐pollination and seed multiplication. The community of pollinators was composed of four bee species and twelve true fly species. Episyrphus balteatus, Eupeodes sp., Musca domestica and Eristalinus aeneus were the most abundant pollinators. The maximum poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Hoverflies are a characteristic fly during the spring (March–April) in this part of Pakistan. Sajjad et al (2010) reported interactions of 14 hover fly species with 59 plant species throughout the year, whereas Saeed et al, 2012, Saeed et al, 2008, Ali et al, 2011 reported the relative effectiveness of different syrphid flies for the pollination of onion, canola, and bitter gourd crops.…”
Section: Discussionmentioning
confidence: 99%
“…Hoverflies are a characteristic fly during the spring (March–April) in this part of Pakistan. Sajjad et al (2010) reported interactions of 14 hover fly species with 59 plant species throughout the year, whereas Saeed et al, 2012, Saeed et al, 2008, Ali et al, 2011 reported the relative effectiveness of different syrphid flies for the pollination of onion, canola, and bitter gourd crops.…”
Section: Discussionmentioning
confidence: 99%
“…Saeed et al (2008) observed the syrphid as a rapid visitor of loquat flowers. However, house fly and carpenter bee spent statistically similar landing times as each other.…”
Section: Discussionmentioning
confidence: 99%
“…This study indicated that syrphid fly, house fly and carpenter bee are rapid fliers. Saeed et al (2008) observed the syrphid as a rapid visitor of loquat flowers.…”
Section: Discussionmentioning
confidence: 99%
“…Flower visitation time of insect not only depend on their species but also on crops. Saeed et al (2008) reported that the syrphid flies were the rapid visitors on loquat flowers. Amin et al (2015) found that the syrphid fly spent shortest duration, and horse fly and sulphur butterfly spent statistically similar and longer duration on mango flower.…”
Section: Resultsmentioning
confidence: 99%